Five‐year audit of adherence to an anaesthesia pre‐induction checklist. (18th March 2022) - Fuchs, A.; Frick, S.; Huber, M.; Riva, T.; Theiler, L.; Kleine‐Brueggeney, M.; Pedersen, T. H.; Berger‐Estilita, J.; Greif, R.
Summary: Although patient safety related to airway management has improved substantially over the last few decades, life‐threatening events still occur. Technical skills, clinical expertise and human factors contribute to successful airway management. Checklists aim to improve safety by providing a structured approach to equipment, personnel and decision‐making. This audit investigates adherence to our institution's airway checklist from 1 June 2016 to 31 May 2021. Inclusion criteria were procedures requiring airway management and we excluded all procedures performed solely under regional anaesthesia, sedation without airway management or paediatric and cardiovascular surgery. The primary outcome was the proportion of wholly performed pre‐induction checklists. Secondary outcomes were the pattern of adherence over the 5 years well as details of airway management, including: airway management difficulties; time and location of induction; anaesthesia teams in operating theatres (including teams for different surgical specialities); non‐operating theatre and emergency procedures; type of anaesthesia (general or combined); and urgency of the procedure. In total, 95, 946 procedures were included. In 57.3%, anaesthesia pre‐induction checklists were completed. Over the 5 years after implementation, adherence improved from 48.3% to 66.7% (p < 0.001). Anticipated and unanticipated airway management difficulties (e.g. facemask ventilation, supraglottic airway device or intubation) defined by the handling anaesthetist were encountered in 4.2% of all procedures. Completion of the checklist differed depending on the time of day (61.3% during the day vs. 35.0% during the night, p < 0.001). Completion also differed depending on location (66.8% in operating theatres vs. 41.0% for non‐operating theatre anaesthesia, p < 0.001) and urgency of procedure (65.4% in non‐emergencies vs. 35.4% in emergencies, p < 0.001). A mixed‐effect model indicated that urgency of procedure is a strong predictor for adherence, with emergency cases having lower adherence (OR 0.58, 95%CI 0.49–0.68, p < 0.001). In conclusion, over 5 years, a significant increase in adherence to an anaesthesia pre‐induction checklist was found, and areas for further improvement (e.g. emergencies, non‐operating room procedures, night‐time procedures) were identified.